2010
DOI: 10.1029/2010gl043472
|View full text |Cite
|
Sign up to set email alerts
|

Global trends in extremal microseism intensity

Abstract: Globally ubiquitous seismic background noise peaks near 7 and 14 s period are generated via distinct mechanisms that transfer storm‐generated gravity wave energy to the seismic wave field. We utilize continuous digital ground motion data recorded by the Global Seismographic Network and precursor instrumentation to chronicle microseism power extreme events for 1972–2009. Because most land‐observed microseism surface‐wave energy is generated at or near coasts, microseism metrics are particularly relevant to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 25 publications
0
58
0
Order By: Relevance
“…So the jumping of the en enchelon pattern and the abrupt changes of that ratio can be used to monitor the turning of a typhoon in near real time. Aster et al (2008Aster et al ( , 2010 and Bromirski and Kossin (2008) have demonstrated that it is possible to use available seismograms to study historic trends of extreme tropical cyclones and their implication in terms of global warming. Lessons learned from this study can also be applied to seismic waveforms recorded before the satellite era to study decadal-scale climate changes.…”
Section: Discussionmentioning
confidence: 99%
“…So the jumping of the en enchelon pattern and the abrupt changes of that ratio can be used to monitor the turning of a typhoon in near real time. Aster et al (2008Aster et al ( , 2010 and Bromirski and Kossin (2008) have demonstrated that it is possible to use available seismograms to study historic trends of extreme tropical cyclones and their implication in terms of global warming. Lessons learned from this study can also be applied to seismic waveforms recorded before the satellite era to study decadal-scale climate changes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is now possible to perform longitudinal studies of station performance in order to identify degradation or mis-installation of seismic equipment (e.g., www.ldeo.columbia.edu/ ~ekstrom/Projects/WQC.html). Long-term noise analysis also provides insight into the evolution of the ocean wave climate, specifically whether the frequency and intensity of storms have changed as global temperatures have changed (Bromirski et al, 1999;Grevemeyer et al, 2000;Aster et al, 2008Aster et al, , 2010Koper et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These advantages explain the recent keen interest in exploiting seismic noise to illuminate the elastic structure of the earth [ Shapiro and Campillo , ; Shapiro et al ., ; Sabra et al , ] and its transient variations attributable to volcanic and seismic activity [ Brenguier et al ., , ; Durand et al ., ; Rivet et al ., ]. Taking advantage of the link between sea states and microseisms, noise records are also analyzed to detect seasonal or long‐term variations, interpreted in turn as changes in climate [ Bromirski et al ., ; Grevemeyer et al ., ; Aster et al ., , ; Stutzmann et al . , ; Ebeling and Stein , ; Ardhuin et al ., ; Traer et al ., ].…”
Section: Introductionmentioning
confidence: 99%